“VOCÊ NÃO PRECISA MAIS DE MIM.” O SER, O PAI E A MORTE EM DAYTRIPPER - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The present work aims to analyze the work Daytripper (2011), by Fabio Moon and Gabriel Bá, and colors of Dave Stewart, attending to the elements that are part of the theme of being, the relationship between father and son and the death. In order to do so, a study was carried out on the configuration of the language of sequential art, enabling dialogues ranging from its macrostructure, with Thierry Groensteen's (2015) theory, to more specific aspects of the internal elements to the picture, using some analytical aspects of semiotics. In the investigation of the thematic aspects about being, father and son and death, we focus mainly on the concepts presented in Being and Time (2012), by the German philosopher Martin Heidegger, relating his arguments with some literary works that raise the themes in question. In this work, we combine the aspects of the language of the graphic novel that dialogue directly with the argumentation provided by it, uniting, in analysis, form and content.
Keywords: Daytripper; Histórias em quadrinhos; Graphic novel; Daytripper; Comics; Graphic novel; CNPQ::LINGUISTICA, LETRAS E ARTES